The Aging of the Population and the Size of the Welfare State - Swagel, Phillip (IMF Working Papers; Working Paper ;, 2002)
Data for the United States and countries in Western Europe indicate a negative correlation between the dependency ratio and both labor tax rates and the generosity of social transfers, after controlling for other factors that influence the size of the welfare state. This is despite the increased political clout of the dependent population implied by the aging of the population. This paper develops a model of intra-and inter-generational transfers and human capital formation which addresses this seeming puzzle. We show that with democratic voting, a higher dependency ratio can lead to lower taxes or less generous social transfers.